Efficient Perovskite/Silicon Tandem Solar Cells on Industrially Compatible Textured Silicon - Luo, Xin; Luo, Haowen; Li, Hongjiang; Xia, Rui; Zheng, Xuntian; Huang, Zilong; Liu, Zhou; Gao, Han; Zhang, Xueling; Li, Songlin; Feng, Zhiqiang; Chen, Yifeng; et al. (Advanced materials (Weinheim), 2023)
Monolithic perovskite/silicon tandem solar cells promise power‐conversion efficiencies (PCEs) exceeding the Shockley‐Queisser limit of single‐junction solar cells. The conformal deposition of perovskites on industrially feasible textured silicon solar cells allows for both lowered manufacturing costs and a higher matched photocurrent density, compared to state‐of‐the‐art tandems using front‐side flat or mildly textured silicon. However, the inferior crystal quality of perovskite films grown on fully‐textured silicon compromises the photovoltaic performance. Here, an anion‐engineered additive strategy is developed to control the crystallization process of wide‐bandgap perovskite films, which enables improved film crystallinity, reduced trap density, and conformal deposition on industrially textured silicon. This strategy allows the fabrication of 28.6%‐efficient perovskite/silicon heterojunction tandem solar cells (certified 27.9%, 1 cm2). This approach is compatible with the scalable fabrication of tandems on industrially textured silicon, demonstrating an efficiency of 25.1% for an aperture area of 16 cm2. The anion‐engineered additive significantly improves the operating stability of wide‐bandgap perovskite solar cells, and the encapsulated tandem solar cells retain over 80% of their initial performance following 2000 h of operation under full 1‐sun illumination in ambient conditions. Herein, an anion‐engineered additive strategy is reported to modify the crystallization process of perovskite films on industrially feasible double‐side textured silicon, which enables conformal deposition with improved film crystallinity and reduced trap density. This allows the fabrication of perovskite/silicon tandem solar cells with efficiencies of 28.9% (certified efficiency of 27.9%) and 25.1% for areas of 1 and 16 cm2, respectively.